Desenvolvimento de método para determinação de resíduos de pesticidas em alface (Lactuca sativa L.) produzida em sistema convencional - Silva, Rogério Luiz da (2010)
Lettuce (Lactuca sativa) has a great, being mainly consumed in natura. In order to ensure greater productivity, pesticides from different chemical classes have been used to improve its production. Although these pesticides bring benefits, increasing agricultural production, their toxicity should be considered. As for this reasor it is necessary to have effective analytical methods to verify the presence of pesticide residues in lettuce. The literature presents Few methods are present in the liberahone for determining pesticides in lettuce. Thus, this paper aims to develop a new method based on MSPD and GC-MS. Techiniques to determine residues of malathion, parathion methyl, pirimicarb, procymidone , α-endosulfan and β-endosulfan in lettuce. The method dispersion matrix solid phase was developed and tested for different types and amounts of sorbents, alumina, Florisil, silica, and organic solvents (20 and 30 mL) and cyclohexane, dichloromethane, ethyl acetate, n-hexane and acetonitrile at different ratios (1:1, 7:3, 8:2, 9:1, 85:15, v/v). The best recoveries for the pesticides malathion, parathion methyl, pirimicarb, procymidone, α-endosulfan and β-endosulfan were obtained through the system silica / alumina, using a volume of 30 mL of acetonitrile with average recovery ranging from 50 to 120% and coefficients of variation varying from 0,6 to 8.0% for concentration levels of 0.1, 0.25, 0.5, 1.0, 1.5 and 2.0 μg g-1 The limits of detection and quantification for the method were 0.08 and 0.11 μg g-1, respectively.